Simple Microcontact Printing Technique to Obtain Cell Patterns by Lithography Using Grayscale, Photopolymer Flexographic Mold, and PDMS - Gimenez, Rocio (2022)
Microcontact printing using PDMS embossing tools and its variations have aroused the interest of a wide spectrum of research fields, hence the feasibility of defining micro and nanoscale patterns. In this work, we have proposed and demonstrated a novel lithography method based on grayscale patterns printed in a flexographic photopolymer mold and transferred to epoxy resin and a single PDMS stamp to obtain different microprint pattern structures. The geometry of the patterns can be modified by adjusting the layout and grayscale of the stamp patterns. The functionality of this contact printing methodology was validated by generating human induced pluripotent stem cells (hiPSC) patterns. These specific micropatterns can be very useful for achieving complex differentiation in cell lines such as hiPSC. Microfabrication through the new technique provides a promising alternative to conventional lithography for constructing complex aligned surfaces; these structures could be used as components of biological patterns or microfluidic devices.